2020
DOI: 10.1002/adfm.202000849
|View full text |Cite
|
Sign up to set email alerts
|

Silica Nanostructures Produced Using Diatom Peptides with Designed Post‐Translational Modifications

Abstract: Diatoms produce intricately-patterned silica structures under ambient conditions, a process initiated by post-translationally modified silaffin peptides that nucleate silicic acid. Designing these peptides would enable the production of silica nanostructures with desired properties; however, the functional effects of modifications are poorly understood. Here, Escherichia coli is used to express and modify recombinant silaffin R5 peptide from the diatom Cylindrotheca fusiformis. A library of 38 enzymes is teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 133 publications
1
28
0
Order By: Relevance
“…[ 97,98 ] The silica‐nucleating silaffin R5 peptide (19 amino acids) from Cylindrotheca fusiformis has been produced recombinantly in E. coli and used to create engineered silica nanostructures. [ 99 ] Natural silaffin polypeptides are highly decorated with post‐translational modifications, but it has been shown that the lysines in unmodified R5 peptides bind to the substrate tetramethyl orthosilicate (TMOS) and are sufficient to catalyze silica precipitation. [ 99,100 ] We hypothesized that the R5 peptide could form a silica shell around nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 97,98 ] The silica‐nucleating silaffin R5 peptide (19 amino acids) from Cylindrotheca fusiformis has been produced recombinantly in E. coli and used to create engineered silica nanostructures. [ 99 ] Natural silaffin polypeptides are highly decorated with post‐translational modifications, but it has been shown that the lysines in unmodified R5 peptides bind to the substrate tetramethyl orthosilicate (TMOS) and are sufficient to catalyze silica precipitation. [ 99,100 ] We hypothesized that the R5 peptide could form a silica shell around nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…[ 99 ] Natural silaffin polypeptides are highly decorated with post‐translational modifications, but it has been shown that the lysines in unmodified R5 peptides bind to the substrate tetramethyl orthosilicate (TMOS) and are sufficient to catalyze silica precipitation. [ 99,100 ] We hypothesized that the R5 peptide could form a silica shell around nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Protein class Description Reference Silicatein A bioorganic–inorganic hybrid material is produced by the incorporation of nanoparticles into sponge spicules [ 73 ] Bacterial biofilm protein (CsgA), silaffin A diatom frustule-like structure is built by harnessing a curli biofilm protein, a chitin-binding domain, and a silaffin peptide, which together serve as a scaffold for silica mineralization. The construction of an artificial photosynthesis system is achieved upon colonization of the material with living cells [ 74 ] Silaffin Recombinant silaffin peptides from diatoms, which nucleate the formation of silica nanostructures, are produced in E. coli with different post-translational modifications, obtaining nanostructures with different properties [ 75 ] A genetically engineered diatom produces silaffin peptides fused to proteins of interest, resulting in the immobilization of the protein in the diatom silica [ 75 ] A genetically engineered diatom produces a silica matrix displaying antibodies on its surface. This material is applied for the targeted delivery of chemotherapeutic drugs [ 76 ] A genetically engineered diatom produces a silica matrix that incorporates proteins of interest.…”
Section: Engineering Cells To Synthesize (Precursors Of) Non-living Materialsmentioning
confidence: 99%